Optimization and analysis of surface flashover triggered vacuum switch conduction delay time characteristics - Ming Zhang; Minfu Liao; Liang Bu; Gang Lu; Longfei Yu; Yifan Sun; Xiongying Duan (AIP Advances)
The conduction delay time is one of the main technical parameters of the surface flashover triggered vacuum switch (STVS). Detailed research and optimization of conduction delay time characteristics are necessary for the development of high-performance STVS. In this paper, the conduction performance of STVS with different electrode structures and operating parameters is investigated in detail. Based on the analysis of the conduction process, the factors affecting the STVS conduction delay time are discussed. The experimental platform is built by using a detachable vacuum chamber, and the conduction delay time characteristics of STVS are compared under different electrode structures and operating parameters. This research analyzes and discusses the reasons for the influence of electrode structures and operating parameters on conduction delay time. The experimental results show that the structure with the trigger gap flashover surface parallel to the cathode surface has a better conduction delay time than the structure with both perpendicular to each other. Both reducing the trigger electrode embedment depth and extending the trigger gap flashover surface length can optimize the conduction delay time of STVS. However, increasing the trigger gap flashover surface length only reduces the conduction delay time at the initial stage of STVS operation. The shorter the main gap distance, the smaller the conduction delay time of the STVS. In addition, increasing the trigger current and operating voltage can diminish the conduction delay time of STVS.